Faktor-faktor yang mempengaruhi prestasi kerja di syarikat xyz - Johari, Md Yusof (2019)
The many successes and excellences that have been shown by this XYZ Company since its inception. Despite the many successes the company has earned, there are also problems that occur in the company as a result of their individual and organizational performance. In this regard, the purpose of the study is to evaluate the factors that contribute to the improvement and reduction of work performance among its employees and to see the demographic differences and the relationship with work performance. This study consists of quantitative research using survey method (questionnaire). Collecting data through questionnaires involved 216 samples among supervisory staff at XYZ Company. Data obtained in this study were then analyzed using the Statistical Package for Social Sciences (SPSS) 23.0. The results show that the overall performance level among employees in XYZ Company is high. In relation to the differences between demographics and work performance shows that there is no significant difference. In contrast, the relationship between performance work and its factors shows that it has a significant relationship. Therefore, these new findings can be used as references to renewing or improving the policies, policies and charter of companies such as making planning training by making more structured training and as inputs to identify the needs or capacity of human resources will increase in the future.